Nucleotide Oligomerization Domain-like receptor 4 (NLR4) Gene Expression and Interleukin 1-β (IL 1-β) Level in Urine Samples Before and After Intravesical BCG Therapy For Treatment of Bladder Cancer - Ahmed Samar Abd Elmoaty Eissa; Ossama Rasslan; Lamia Fouad; Fahim Hisham Abdelmajeed; Amira Esmail Abdel-Hamid (Медицинская иммунология, 2021)
Bladder cancer is the 7th most commonly diagnosed cancer in males worldwide and the 11th when both genders are considered. Seventy five per cent of bladder cancer cases are non-muscle invasive bladder cancer (NMIBC). Bacillus Calmette–Gu rin (BCG) immunotherapy remains the standard intravesical agent for NMIBC. The exact mechanism by which BCG prevents recurrence is unknown. The aim of this study was to evaluate NLR4 gene expression and IL-1β as possible prognostic indicators for NMIBC recurrence and BCG treatment failure, and to detect the difference in their levels among muscle invasive bladder cancer (MIBC) and NMIBC that may aid in primary differentiation between cases. This study was conducted in 30 patients who had NMIBC and 17 patients who had MIBC. Urine samples were obtained in sterile cups before operation. From NMIBC cases, four more samples were obtained as mentioned below. Evaluation of NLR4 gene expression was performed in pre-surgical sample for MIBC and in 4 samples for NMIBC: pre-surgical sample, sample collected 4 hours after the 3rd dose of BCG instillation, and samples collected during follow up (3 and 6 months post-surgically). There was statistical significant increase in NLRP4 expression levels in NMIBC (CT=0.87±1.48) compared to MIBC (CT=2.82±2.07). As far as we searched, no published results were found regarding comparative gene expression levels between NMIBC and MIBC cases. Gene expression in recurrent cases was higher in pre-surgical urine samples than in non-recurrent cases. The expression level further increased up to 21 fold than the pre-surgical level in the sample taken after injection of the 3rd dose of BCG. This level decreased distinctly to become 1-fold increase over pre-surgical level at the 3rd month follow up then to only 0.9-fold at the 6th month. In non- recurrent cases, gene expression level started pre-surgically in much lower levels than those encountered in recurrent cases. There were 11-fold increase in expression level after 3rd dose of BCG instillation and then decreased to be 5.6 folds higher in the sample taken at 3rd month follow up than in presurgical samples. Gene expression further decreased to become 4.1 fold higher in samples taken at 6 month follow up than the pre-surgical levels. IL-1β levels were estimated for NMIBC and MIBC cases in urine samples pre-surgically and during BCG therapy in case of NMIBC before and 4 hours after the 3rd dose and during 3rd month follow-up of those cases for searching its possible use of for primary differentiation between NMIBC and MIBC, and also as a prognostic factor for possible recurrence in case of NMIBC cases. The level of IL-1β was generally higher in pre-surgical samples (0.62±0.12 pg/ml) when compared to its level before the 3rd dose of BCG induction therapy (0.53±0.13 pg/ml). Its level was distinctly higher four hours after administration of the 3rd dose BCG (1.96±0.62 pg/ml) than both previous levels. Levels decreased bellow pre-surgical level at 3rd month follow up (0.57±0.099 pg/ml). The levels of IL-1β estimated in samples collected four hours after the 3rd dose BCG was higher in cases that showed recurrence later on than non-recurrent cases. The levels decreased in both cases and became higher in non-recurrent cases (0.64±0.05 pg/ml) than in cases already developed recurrence at the 3rd month diagnosed during follow-up (0.45±0.05 pg/ml). To conclude, on following NLRP4 gene expression and IL-1β levels during BCG administration among recurrent and non-recurrent cases of thirty NMIBC cases, there was a significant statistical difference in both levels for the samples collected after the third dose BCG, being higher in patients who showed subsequent recurrence at the 3rd and 6th month of follow-up. If these preliminary reported findings will be confirmed in upcoming larger cohort’s studies, it could be promising in prognosis of such cases, with the possibility of early manipulation of individualized treatment schedule, keeping patients most probably prone to encounter recurrence safe from possible side effects of BCG therapy. The assessment of NLRP4 expression and IL-1β levels could help predict failure of BCG therapy, playing an appreciable role in early deciding radical surgery. When comparing NLRP4 expression and IL-1β levels between MIBC and NMIBC cases, increased values were noted among non-invasive ones. This finding may serve as a possible diagnostic tool, which represents a challenging issue. Hence, cut-off values for gene expression and cytokine level are to be specified.